136k views
2 votes
Solve the equation.

5x + 6 = 2(2x – 3)

User Steve Peak
by
5.6k points

2 Answers

5 votes

Answer:

x=-12

Explanation:

User Rob Bazinet
by
5.3k points
4 votes

Answer: x=-12

Explanation:

To solve the equation you must solve for x, then you must apply the following proccedure;

- You must apply the distributive property.

- Subtract 4x from both sides of the equation.

- Subtract 6 from both sides of the equation.

Therefore, you obtain the following result:


5x+6=4x-6\\5x-4x=-6-6\\x=-12

User Chris Rae
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.